Reversed-Phase HPLC Characterization and Quantification and Antioxidant Capacity of the Phenolic Acids and Flavonoids Extracted From Eight Varieties of Sorghum Grown in Austria - Speranza, Sofia; Knechtl, Rebecca; Witlaczil, Ragnar; Schönlechner, Regine (Frontiers in Plant Science, 2021)
Sorghum is raising great interest as grain for the future, for its agricultural advantages in times of climate change and for the positive impact on human health of its bioactive compounds. These comprise phenolic acids, in free, conjugated and bound form, and flavonoids. The most commonly used extraction methods require high volumes of chemicals and are not practical when handling many samples at a time. The main aim of this study was to develop a micro-scale extraction procedure for both phenolic acids and flavonoids to improve yield and diversity, labor time and chemicals usage. The improved protocols allowed to perform the extraction in 2 mL safe-lock tubes using around 60 times less chemical volume for the phenolic acids and 6 times less for flavonoids. In addition, the micro-scale approach was effective in extracting a comparable amount of phenolic acids (between 0.99 mg FA/g, and 1.57 mg FA/g) and an even higher quantity of flavonoids (between 1.10 mg FA/g and 2.24 mg FA/g), compared to the macro-scale method. With the established methods, phenolic compounds were extracted from 8 varieties of sorghum grown in Austria, previously shown promising for food processing. In all sorghum varieties protocatechuic, vanillic, caffeic, syringic, P-coumaric and ferulic acids were detected in free, conjugated and bound form, with the latter being the most abundant. The Arsky and Icebergg varieties presented the lowest (922.65 µg/g) and the highest (1269.28 µg/g) levels of total phenolic acids, respectively, recorded with the HPLC. Flavonoids, comprising luteolinidin, apigenidin, naringenin, apigenin, 5-MetO-Lut and 7-MetO-Api were detected in amounts between 27.03 µg/g (Kalatur variety) and 87.52 µg/g (Huggo variety). The red varieties, Huggo, Armorik and Arsky, had the highest antioxidant activity measured as DPPH (around 5.00 µg TE/g) and ABTS (around 3.00 µg TE/g) scavenging capacity for both phenolic acids and flavonoids. FRAP was the highest for the phenolic acids extracted from the white Ggolden variety.